Green Synthesis of Silver Nanoparticles Loaded With Activated Carbon and Its Characterization - R. Sharmila Devi; C. Sebastian Antony Selvan (International Journal of Research in Chemistry and Environment (IJRCE), 2015)
In this study, a new adsorbent, the greener synthesis of silver nanoparticles loaded with activated carbon (Ag-NP-AC) was synthesized and characterized. This novel material was characterized and identified by different techniques such as FTIR,Scanning Electron Microscopy(SEM),XRD analysis. Surface functional groups were detected by Fourier transformation infrared (FTIR) spectroscopy techniques. The surface morphology, porosity of silver nanoparticle loaded activated carbon was visualized via scanning electron microscopy (SEM) analysis .The nature of the particles determined by X-ray diffraction method.